KU60019 inhibits ovarian cancer progression by targeting DGAT1/has-miR-1273g-3p axis. - Zhanchuan Ma; Rongjing Dang; Guodong Wu (PLoS ONE)
Ataxia telangiectasia mutated (ATM) blockage can induce apoptosis in ovarian cancer. However, the molecular mechanisms underlying this process remain poorly understood. In this study, ovarian cancer cells (SKOV3) were treated with an ATM inhibitor (KU60019) for 24 hours, and the fold changes of DGAT1 and hsa-miR-1273g-3p were quantified by real-time quantitative polymerase chain reaction (RT-qPCR). Gene Ontology (GO) and pathway enrichment analyses of DGAT1-associated functions were performed. Hsa-miR-1273g-3p mimics were used to investigate the relationship between DGAT1 and hsa-miR-1273g-3p in ovarian cancer cells under ATM inhibitor treatment, and cell apoptosis rate, viability, and migration were detected. The DGAT1 inhibitor reversed KU60019-induced migration impairment in SKOV3 cells. Finally, Kaplan-Meier analysis showed the correlation between DGAT1 level and survival in ovarian cancer patients. We found that ATM blockage significantly suppressed hsa-miR-1273g-3p level and elevated DGAT1 level in SKOV3 cells. DGAT1 was enriched in cytokine receptor interaction, T cell receptor signaling pathway, and cell apoptosis. Hsa-miR-1273g-3p mimics reversed suppression of DGAT1 and impaired cell viability induced by KU60019. Higher levels of DGAT1 associated with worse survival in ovarian cancer patients. KU60019 induced ovarian cancer cell impairment by enhancing DGAT1 level and suppressing hsa-miR-1273g-3p level. Our results demonstrate the antitumor effect of KU60019 in ovarian cancer depended on miR1273g-3p/DGAT1 axis.